Role of university extension in agricultural vocational formation - Hernández Medina, Carlos (2020)
The principles of University Extension were used in Children's Vocational Formation in the Primary School "Juan Francisco Aro" of Vega Alta, Camajuaní, Villa Clara, with methodological support of the Municipal University Center (MUC). Activities of professors' and relative´s training were organized to prepare the students in love to plants, sustainable agriculture, reforestation, use of organic fertilizers and consumption of healthy foods cultivated in the school orchard. The cloister deepened in the values responsibility and planning to improve the quality of the formative process of childrens.